Green chemistry approach to styrene from ethylbenzene and air on MnxTi1-xO2 catalyst - Negi, Sanjay Singh; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy; Singh, Anand Pal; Gopinath, Chinnakonda S. (RSC Advances, 2014)
Styrene (ST) is an industrially important commodity chemical, and design of a suitable catalyst, which provides high ethyl benzene (EB) conversion and styrene selectivity at Lower temperature with sustainable activity, is one of the major challenges in the field of heterogeneous catalysis. Manganese incorporated in titania (MnxT1-xO2) anatase Lattice, prepared via the solution combustion method, was evaluated for oxidative dehydrogenation (ODH) of EB with O-2 or air. MnxTi1-xO2 catalysts were characterized by different physiochemical methods. Up to 15% Mn could be introduced into the TiO2 Lattice. TEM and XRD indicate disordered mesoporosity, further confirmed by adsorption isotherm analysis. MnxTi1-xO2 catalysts were evaluated for ST synthesis from EB using air or oxygen as oxidant between 440 and 570 degrees C. Reaction conditions have been varied systematically, such as catalyst composition, and EB/air/O-2 flow. MnxTi1-xO2 shows sustainable 55% styrene yield for 45 h without deactivation under optimum conditions. A thorough analysis of spent catalysts demonstrates the conversion of initial anatase phase MnxTi1-xO2 to Mn3O4 supported on the rutile (R) phase of TiO2. The above change occurs in the first few hours of reaction and the Mn3O4 on R-TiO2 phase is the active phase of the catalyst and responsible for sustainable activity for Longer duration.

Green synthesis of cyclohexanone to adipic acid over Fe-W oxides incorporated mesoporous carbon support - Mekala, Siva Prasad; Prabu, Marimuthu; Gawali, Sheetal Datta; Gopakumar, Karthik; Gogoi, Pranjal; Bhatkar, Akash Ravindra; Mohapatra, Gourab; Unnikrishanan, Eeswar; Raja, Thirumalaiswamy (Catalysis Communications, 2022)
We have prepared iron and tungsten oxides incorporated mesoporous carbon (MC) catalysts using a simple hydrothermal methodology with different carbon sources, and the catalytic performance was investigated for cyclohexanone oxidation. An adequate amount of metal oxide loading has displayed a key role in the selective catalyst for adipic acid (AA) synthesis. The MC catalyst has shown its prime activity under the influence of redox properties of W5+/W6+ and Fe2+/Fe3+ as promoters. The 10%Fe 90%W-MC fructose as a carbon source catalyst has provided its best selectivity of 87% for AA at 120 ?C.
Keywords: Adipic Acid; Liquid phase oxidation; mesoporous carbon; Redox center